Personality profile of successful entrepreneurs - Shinta Setia (Universitas Hayam Wuruk Perbanas, 2018)
Working as entrepreneurs has become popular in Indonesia in recent years. The reason is not only they are deemed to be as a hero by the society, but also they are seen as an alternative career by young generation. This is due to their being quite attractive in terms of time flexibility as well as their potential income.Â People have seen a fact that job opportunities and the competition in the market are getting more and more competition. Therefore, entrepreneurs seem to be an alternative promising career, Supported by modern technology, e-commerce era, digital life style have indeed provided more positive hopes being an entrepreneur, The objective of this research is to examine the influence of personality towards successful entrepreneur. The personality of entrepreneur is based on The Big Five Model of Personality translating personality into 5 different profiles: conscientiousness, openness to experience, extraversion, agreeableness and emotional stability. Sample of this research are 39 successful entrepreneurs, measured by its business growth, profit and turnover growth, employment growth, and length of company's survival. Result indicated that 1 out of 5 personality dimensions: conscientiousness showed the strongest significant correlation to successful entrepreneurs.Â